Development and Evaluation of Stability of a Gel Formulation Containing the Monoterpene Borneol. (9th May 2016) - Dantas, Milla Gabriela Belarmino; Reis, Silvio Alan Gonçalves Bomfim; Damasceno, Camila Mahara Dias; Rolim, Larissa Araújo; Rolim-Neto, Pedro José; Carvalho, Ferdinando Oliveira; Quintans-Junior, Lucindo José; Almeida, Jackson Roberto Guedes da Silva
Abstract : Borneol is a bicyclic monoterpenoid alcohol commonly used in traditional Chinese and Indian medicine. It is extracted from the essential oil of various medicinal plants. It has antibacterial, analgesic, and anti-inflammatory action proven in studies that used oral and intraperitoneal applications of this monoterpene in mice. The current study was designed to develop a topical gel formulation containing the monoterpene borneol using carbopol as gel base and to evaluate its stability. The prepared formulation was subjected to physical characterization and physical-chemistry assessment. The gel was prepared from carbopol and 5% of borneol. The prepared gel was subjected to pharmacotechnical tests such as its pH, viscosity, conductivity, spreadability, centrifugation, and accelerated stability with freezing-thaw cycle. The borneol was successfully incorporated into the carbopol formulation. Borneol gel (BG5) showed good stability after eight months of its development and after 12 days in the freeze-thaw cycle, not showing statistical difference in pH value, conductivity, and viscosity before and after test. Furthermore, the formulation showed a good spreadability. Therefore, it was concluded that the formulation could be very promising alternative for the topical or transdermal treatment of skin diseases.